Implementasi Kegiatan Pagi dalam Meningkatkan Disiplin Siswa di SD Negeri 026 Huraba - Akhrif Yahsya; Muhammad, Fazlur; Novita Rahmadani; Nurhakikah; Ici lassie Rahmah Rama Dhani; Khoirunnisah Hsb; Muhammad Pauzan; Nur Azizah Pulungan; Abdur Rahman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the implementation of morning activities in improvingstudent discipline at SDN 026 Huraba through Field Experience Practice (PPL). Field observations indicate that SDN 026 Huraba implements various forms of positive habits that involve students from the very start of daily activities. These activities begin with a morning greeting, a group prayer, singing the national anthem, and a 10-minute literacy sessionbefore instruction begins. Teachers involvestudents in monitoringclassroom cleanlinessand the orderlinessof seating arrangements. Research findings indicate that morningactivities have a positive impact on improving student discipline. This isevident in increased punctuality, neatness of attire,compliance with rules, and active participation in school activities.In addition, religious activities such as reciting the Yasin also play a role inshaping students’ religious character. Habits formed through daily routinesare able to instill a disciplined attitude gradually withoutcoercion. Thus, the implementation of morning activities can be one of theeffective strategies for improving student discipline in elementary schools.